2006
DOI: 10.1194/jlr.m600120-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of CYP7A1 in LDL receptor-deficient mice blocks diet-induced hypercholesterolemia

Abstract: Constitutive expression of a cholesterol-7a-hydroxylase (CYP7A1) transgene in LDL receptor-deficient mice blocked the ability of a cholesterol-enriched diet to increase plasma levels of apolipoprotein B-containing lipoproteins. LDL receptor-deficient mice expressing the CYP7A1 transgene exhibited complete resistance to diet-induced hypercholesterolemia and to the accumulation of cholesterol in the liver. Hepatic mRNA expression of liver X receptorinducible ABCG5 and ABCG8 was decreased in CYP7A1 transgenic, LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 38 publications
2
25
2
Order By: Relevance
“…In the transcriptome study performed on a subset of the mice (n=3 per diet group) we found that hepatic Cyp7a1 transcript levels were higher in the herring-fed compared with the beef-fed mice (24). That Cyp7a1 is a promising candidate as a mediator for the herring-induced effects is supported by the finding that Ldlr -/-mice overexpressing Cyp7a1 were resistant to diet-induced hypercholesterolemia (40).…”
Section: Discussionsupporting
confidence: 50%
“…In the transcriptome study performed on a subset of the mice (n=3 per diet group) we found that hepatic Cyp7a1 transcript levels were higher in the herring-fed compared with the beef-fed mice (24). That Cyp7a1 is a promising candidate as a mediator for the herring-induced effects is supported by the finding that Ldlr -/-mice overexpressing Cyp7a1 were resistant to diet-induced hypercholesterolemia (40).…”
Section: Discussionsupporting
confidence: 50%
“…Overexpression of CYP7A1 blocks the increase in hepatic lipids that occurs when LDLR 2/2 mice are fed a Western diet (14). The LDLR 2/2 SHP 2/2 mice did not have reduced hepatic lipid levels nor altered patterns of cholesterol regulated gene expression.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, there is also an inverse correlation between CYP7A1 expression and plasma cholesterol levels in primates (13). In mice, transgenic overexpression of CYP7A1 blocks diet-induced hypercholesterolemia and atherosclerosis (14,15). The loss of SHP repression of CYP7A1 expression could thus be predicted to have beneficial effects on LDL cholesterol levels.…”
mentioning
confidence: 99%
“…Adenovirusmediated overexpression of CYP7A1 in the hamster reduces plasma LDL cholesterol in direct proportion to the magnitude of increase in cholesterol-7-a-hydroxylase activity (27). Similarly, transgenic overexpression of CYP7A1 blocks dietinduced atherosclerosis in wild-type and LDLR 2/2 mice (28,29). Generally in these studies, CYP7A1 has been expressed at ?10-fold elevated levels over the already high levels present in the mice.…”
Section: Discussionmentioning
confidence: 99%